THE SOLAR SYSTEM : OUT OF THIS WORLD WITH SCIENCE ACTIVITIES FOR KIDS - Lopez, Delano; Slater, Jason (White River Junction, Vermont : Nomad Press, a division of Nomad Communications, 2019)
c ack cover.
Includes bibliographical references (pages 116-118) and index.
Keywords: Science projects -- Juvenile literature; Solar system -- Juvenile literature. -- Experiments